Cystic fibrosis transmembrane conductance regulator is an epithelial cell receptor for clearance of Pseudomonas aeruginosa from the lung - Pier, Gerald B. (The National Academy of Sciences of the USA, 1997)
The cystic fibrosis transmembrane conductance regulator (CFTR) is a chloride ion channel, but its relationship to the primary clinical manifestation of CF, chronic Pseudomonas aeruginosa pulmonary infection, is unclear. We report that CFTR is a cellular receptor for binding, endocytosing, and clearing P. aeruginosa from the normal lung. Murine cells expressing recombinant human wild-type CFTR ingested 30–100 times as many P. aeruginosa as cells lacking CFTR or expressing mutant ΔF508 CFTR protein. Purified CFTR inhibited ingestion of P. aeruginosa by human airway epithelial cells. The first extracellular domain of CFTR specifically bound to P. aeruginosa and a synthetic peptide of this region inhibited P. aeruginosa internalization in vivo, leading to increased bacterial lung burdens. CFTR clears P. aeruginosa from the lung, indicating a direct connection between mutations in CFTR and the clinical consequences of CF.